Optimisation Of Gravure Cylinder Plating By Designing And Fabricating The Cylinder Copper Plating Machine - Ariyono, Sugeng (2000)
The fast growing packaging industry in South-East Asia has provided a great potential for the use of cylinder copper plating machines for printing. The purpose of this project is to design and develop a prototype of an automated fully immersion cylinder copper plating machine capable of functioning at optimum parameters automatically and thus achive enhanced print quality. The development also includes minimising the set-up process and facilitates maintenance by designing leakage blocks and built-in module respectively. Complexity of the plating parameters needed in the gravure industry could have significant influence on the plating process and quality of end product. In this research work the effect of linear cylinder speed and cathode-anode distance on the copper plating efficiency, deposit structure, and hardness has been investigated. The results showed that maximum plating efficiency is affected by both cylinder linear speed and cathode-anode distance. Within the low range of linear speed covered (40 to 105 m/min), the maximum efficiency is achieved for small cathode-anode distance (2 cm). At high linear speeds (106 to 133 m/min), however, the maximum efficiency was observed to occur at higher cathode-anode distance (4 cm). This increase in efficinecy appears to be triggered by agitation in the electrolyte solution. Metallurgical examination revealed that the maximum plating efficiency is associated with finer structures and higher hardness valu